A review on optimization methods applied to energy management system - Graa, Amel; Benhamida, Farid (Serbian Journal of Management, 2020)
Energy is fundamental in supporting people’s daily subsists and the continual mission for human life improvement. The computer-aided instruments system used by electric utility grids or microgrids operators to control, monitor, and optimize the power system operation is generally named Energy Management System (EMS). The topic of optimization methods applied to decision making problems in such system is a difficult and complex combination of mathematical formulation, modeling and algorithmic solution. The best result in such process is applied to the problem to be optimized, which must be studied in great depth. Furthermore, difficult mathematical calculations and procedures can be elaborated; also, computer knowledge and software engineering competences must be provided. The subject of this paper is an overview of the existing important optimization methods used in electric power management system such as unit commitment, optimal power flow and economic dispatch.